Evaluation and transient control of an advanced multi-cylinder engine based on partially premixed combustion. (1st January 2019) - Yin, Lianhao; Turesson, Gabriel; Tunestål, Per; Johansson, Rolf
Highlights: Partially premixed combustion was applied on a multi-cylinder engine. Different injection strategies should be adapted at different engine loads. During stable operations, a peak gross indicated efficiency of 51% was achieved. During transient operations, an average net indicated efficiency of 47.5% was demonstrated. Abstract: Modern transportation requires advanced powertrain systems to reduce the production of greenhouse gas CO2 . Partially premixed combustion (PPC) is one of the most promising methods to achieve low emission and low fuel consumption of internal combustion engines. The present paper evaluated the effects of the calibration parameters on the efficiency and emissions of a multi-cylinder engine using PPC during stable operations, and the performance of the engine during transient operations. The peak gross indicated efficiency of 51.5% and the peak net indicated efficiency of 48.7% were achieved under stable operating conditions. The transient results also demonstrate an average net indicated efficiency of 47.5%. The nitrogen oxides (NOx), carbon monoxide (CO), and hydrocarbon (HC) conform with the Euro VI emission legislation in the case of most transient operations except some low load points.